MINAT GURU SEJARAH TERHADAP PROGRAM PENDIDIKAN GURU PENGGERAK DI PROVINSI BANTEN - Abdul Somad (Universitas Sultan Ageng Tirtayasa, 2022)
This research is based on the recruitment of Driving Teacher Candidates and Practical Teacher Candidates in the Driving Teacher Education Program from the Ministry of Education, Culture, Research and Technology as the implementation of the Independent Learning policy. Researcher want to know how the interest of history teachers in Banten Province towards this program. The methodology used is a quantitative, qualitative and descriptive approach with two instruments, namely questionnaires and interviews. Respondents were 123 teachers, while interviews were conducted with three teachers. The results showed that most of the respondents were interested in registering, both as Driving Teacher Candidates and Practical Teacher Candidates. Intrinsically, the most dominant motivation of applicants is to develop themselves as innovative, creative, professional teachers who implement student-centered learning. As for extrinsically, the biggest influence on the emergence of interest is because of the support from fellow teachers at school. The most interesting finding is that the dissemination carried out by professional teacher organizations or teacher communities through webinars and other online discussion forums has more influence on teacher interest than the dissemination carried out by the Ministry of Education, Culture, Research and Technology as well as from the Banten Province Education and Culture Office. Therefore, stakeholders need to always synergize and collaborate with all parties, especially professional organizations or the teacher community, so that government programs can be carried out optimally.